A NEW CLASS OF ISODUAL CYCLIC CODES OF RATE 1/2 OVER F_p - CHERIF MIHOUBI; PATRICK SOLE (Romanian Journal of Mathematics and Computer Science, 2016)
A new class of isodual cyclic codes of parameters [n, k]_p, is found for n singly even, not a multiple of p